Penerapan Kewajiban Konsumen Untuk Membaca Informasi Barang Berupa Makanan Ringan dan Minuman Dalam Rangka Perlindungan Diri Sebagai Konsumen Berdasarkan Undang- Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen Di Kecamatan Sail - Amaliah, Nadhira; Hasanah, Ulfia; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Consumer protection is a term used to describe the Legal Protection givento consumers in their efforts to meet the needs of the things that could harmconsumers themselves. Consumer protection law exists to protect the consumerthemselves. Consumers are required to be critical using product with considering"needs" rather than "desire". Consumers should be aware of the good’s conditionprovided by businesses. Here the wisdom required consumers to be careful inchecking the condition of the goods as well as a description of the composition, andan expiration date to avoid things that can harm consumers itself when using goods.In order to achieve the objective of consumer protection laws to increaseawareness, ability and independence of the consumers to protect themselves. Thisresearch objective are: First, to determine why consumers do not implement theirobligations in order to protect themselves as consumers, Second, obstacles thatoccur so that consumers do not carry out its obligations, Third, efforts should bedo to raise awareness of consumer.The result of this research are, First, the implementation of the obligationsof consumers in order to protect themselves as consumer has not been fullyimplemented by the consumer, Second, obstacles that occur caused by lack ofconsumer awareness, the lack of information and the dissemination of governmentabout becoming a smart consumer , Third, attempts to do is to conduct counselingto increase knowledge, awareness, and independence of consumers with the help ofrelevant institutions, such as the Institute For Consumer Protection Organization.Suggestions,First, community should to be more active and intelligent and criticalas consumers. Second, the government should be more concern about consumerprotection such as provide public care about consumer protection law, Third, reactivatedthe relevant organization of consumer protection as governmentrepresentatives in representing the consumer voice.Keywords: responsibility, consumers, application